Forest conversion alters the structure and functional processes of tropical forest soil microbial communities. (22nd September 2020) - Lan, Guoyu; Wu, Zhixiang; Yang, Chuan; Sun, Rui; Chen, Bangqian; Zhang, Xicai
Abstract: Many studies have been carried‐out on the effects of forest conversion on soil microbial community composition and diversity. However, impacts on soil microbial functions and how diversity changes across scales are poorly understood. To fill the research gap, we used metagenomic sequencing and 16S rRNA and ITS gene sequences to evaluate the microbial composition, diversity, and function of 260 soil samples collected from tropical rainforest and rubber plantation sites across Hainan Island, South China. The results revealed that: (a) Forest conversion resulted in shifts in microbial composition (from the Proteobacteria to Chloroflexi), archaeal composition (from Thaumarchaeota to Bathyarchaeota), and fungal composition (from Basidiomycota to Ascomycota). (b) Bacterial alpha, beta, and gamma diversity were not reduced by forest conversion. However, fungal beta diversity was lower in the plantations, resulting in a decrease in gamma diversity. Archaeal beta diversity was higher in rainforest versus rubber plantation soils, but archaeal gamma diversity showed the opposite pattern. (c) Soil functional composition and diversity did not differ with forest type; however, genes related to metabolism and degradation processes were significantly more abundant in the tropical rainforest. These changes in gene abundance could alter ecosystem processes. (d) Soil pH and environmental heterogeneity were the main drivers of microbial taxonomic composition and functional gene composition. Land use explained 13.28% of the variation in taxonomic composition but did not explain changes in functional gene composition. We concluded that land use changes can alter soil microbial community structure and have profound effects on ecosystem functions and processes.